2007
DOI: 10.1892/0891-6640(2007)21[508:sbacih]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bile Acids Concentrations in Healthy and Clinically Ill Neonatal Foals

Abstract: SBA concentrations in foals are significantly higher in the early neonatal period, underscoring the importance of using age-matched references when evaluating clinical pathology values during the neonatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 11 publications
3
30
1
4
Order By: Relevance
“…The high levels of unconjugated bilirubin indicated that hemoglobin are too much destroyed. Although in this experiment total bilirubin significantly increased in treatment BW (1.54 mg/dL), but this value was in the normal range of total bilirubin mature in horses (0.1-1.9 mg/dL) (Barton & LeRoy 2007).…”
Section: Serum Biochemical Parameterscontrasting
confidence: 70%
“…The high levels of unconjugated bilirubin indicated that hemoglobin are too much destroyed. Although in this experiment total bilirubin significantly increased in treatment BW (1.54 mg/dL), but this value was in the normal range of total bilirubin mature in horses (0.1-1.9 mg/dL) (Barton & LeRoy 2007).…”
Section: Serum Biochemical Parameterscontrasting
confidence: 70%
“…The working diagnosis for this filly was encephalopathy secondary to gastrointestinal hyperammonaemia. Ammonia is normally produced within the intestinal tract following bacterial degradation of endogenous and exogenous protein, which occurs predominately in the caecum and colon (Wootton and Argenzio 1975; Mair and Jones 1995), where ammonium diffuses into the portal circulation to the liver for removal via the urea cycle (Barton and LeRoy 2007). In some situations, ammonium can accumulate within the circulation, leading to signs of encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…An abdominal ultrasonographic examination revealed no abnormalities. Further biochemical analysis revealed a hyperammonaemia of 159 µmol/l (rr <50 µmol/l in mature horses) and evidence of mild increases in SDH (13.0 u/l, rr 0.7–4.5 u/l) and serum bile acids (17.9 µmol/l, rr 10.6–15.8 µmol/l) (Barton and LeRoy 2007). The CBC revealed a neutrophilia: 23.60 × 10 9 (rr 5.4–12.3 × 10 9 ), consisting of a mature neutrophilia (94% neutrophils) and blood lactate increased to 2.8 mmol/l.…”
Section: Clinical Detailsmentioning
confidence: 99%
“…Comparados com os neonatos equinos, os recém-nascidos asininos da raça Martina Franca possuem contagem de hemácias menor no primeiro dia de vida (7,,15 x10 6 /µL) e com sete dias (7,(1)(2)(3)(4)(5)(6)(7)8 STONEHAM, 2006;GRONDIN;DEWITT, 2010).…”
Section: Revisão De Literaturaunclassified
“…Para asininos, os valores de neutrófilos segmentados ao nascimento (3,(6)(7)6 x10 3 /µl), 1 (2,9-6,7 x10 3 /µl) e 7 dias (4,(6)(7)7 (4,(4)(5)9 g/dL) e asininos (3,(2)(3)(4)(5)(6)6 g/dL) possuem valores inferiores aos de adultos, porém após à ingestão do colostro ocorre um aumento das concentrações, tanto nos equinos (5,2-8,0 g/dL) como nos asininos (3,7 g/dL) . Porém os valores de albumina não sofrem alteração durante os primeiros meses de vida .…”
Section: Revisão De Literaturaunclassified